Effect of Palm Oil Fuel Ash Treated with Citric Acid to Physico-Mechanical Properties of Cement Paste - Mhd Shukri, Nur Syazwani ilyana; Mohamad Zaky Noh, (Enhanced Knowledge in Sciences and Technology, 2024)
The utilization of waste materials in construction materials has gained considerable attention as a sustainable and environmentally friendly practice. This study investigates the application of Palm Oil Fuel Ash (POFA) treated with citric acid as a supplementary cementitious material in cement paste. The untreated POFA (UPOFA) undergoes several processes such as sieving, grinding and heat treatment at 800℃ for 1.5 hours and acid treatment. Accordingly, there are UPOFA, treated POFA (TPOFA) and treated POFA mixed with sand (TPOFA + sand). The maximum density for UPOFA, TPOFA and TPOFA mixed with sand is 20% percentage of POFA both for 7 days and 14 days curing period. As for water absorption for TPOFA mixed with sand is the highest compared to UPOFA and TPOFA.  For 7 days of curing period for compressive strength it rises up until 20% of POFA for UPOFA (32.40MPa), TPOFA (34.41MPa) and TPOFA mixed with sand (38.62MPa). Meanwhile for 14 days of curing period for UPOFA (34.80MPa), TPOFA (36.82MPa) and TPOFA mixed with sand (40.25MPa). The incorporation of treated POFA into cement paste is a promising material that can be used because it improved workability and enhanced the physical and mechanical properties, attributed to enhanced pozzolanic activity. This research contributes valuable insights into the sustainable use of waste materials in cementitious systems, demonstrating the feasibility of enhancing POFA’s performance through citric acid treatment.